2015
DOI: 10.1186/s40981-015-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between succinylcholine and rocuronium as neuromuscular blocking agents for electroconvulsive therapy in a patient with pseudocholinesterase deficiency

Abstract: We report here the anesthetic management of a patient with schizophrenia and pseudocholinesterase deficiency. Electroconvulsive therapy was performed using succinylcholine and rocuronium as the neuromuscular blocking agents in the first seven and latter six treatments, respectively. The recovery time from muscle relaxation after succinylcholine administration was remarkably longer than that after rocuronium-sugammadex administration. Rocuronium and sugammadex appear to be useful in situations in which succinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…10,18 Even at low doses, the combination of rocuronium-sugammadex seems to be an ideal alternative in ECT anesthesia when seizure duration, the incidence of side effects, and hemodynamic parameters are taken into account, especially in cases where succinylcholine is contraindicated. 17 Hemodynamic parameters were similar in both groups. The postoperative period was generally uneventful in both groups, and the patients were discharged from the post-anesthesia care unit approximately 60 minutes later.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…10,18 Even at low doses, the combination of rocuronium-sugammadex seems to be an ideal alternative in ECT anesthesia when seizure duration, the incidence of side effects, and hemodynamic parameters are taken into account, especially in cases where succinylcholine is contraindicated. 17 Hemodynamic parameters were similar in both groups. The postoperative period was generally uneventful in both groups, and the patients were discharged from the post-anesthesia care unit approximately 60 minutes later.…”
Section: Discussionmentioning
confidence: 74%
“…35 On the other hand, Kadoi et al 14 compared rocuronium with 0.6 mg kg -1 and different doses of sugammadex and 1 mg kg -1 of succinylcholine in propofol anesthesia and found no significant difference in seizure duration among all groups. Takazawa et al 17 reported succinylcholine below the normal application dose (0.24±0.23 mg kg -1 ) in the first seven ECT sessions in a schizophrenic patient with pseudocholinesterase deficiency, rocuronium (0.52±0.02 mg kg -1 ) in the next six ECT sessions, and to reverse the block, 200-400 mg sugammadex was used and they reported that seizure duration was not different between succinylcholine and rocuronium-sugammadex. They interpreted that improvement in a depressive state with ECT may affect seizure duration, therefore, the use of rocuronium after succinylcholine may mask ECT seizure duration, which is likely to be longer with rocuronium administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la búsqueda de la alternativa a succinilcolina como relajante neuromuscular en tiroidectomías, se tuvo en cuenta un medicamento que proveyera condiciones seguras y adecuadas, rápida recuperación de la función psicomotora y pocas reacciones adversas; en estos aspectos, rocuronio es el que mejor se perfila [4]. Por tales motivos, el presente estudio tiene por objetivo realizar un análisis farmacoeconómico de tipo costo-efectividad en el que se compararon los períodos de latencia, condiciones de intubación, costos asociados a las variables mencionadas, tiempos de recuperación y reacciones adversas causadas por estos agentes, proporcionando evidencias que permitan un análisis completo al momento de elegir los relajantes neuromusculares que se van a utilizar en tiroidectomías.…”
Section: Introductionunclassified